A Real-World Experience of Mycophenolate Mofetil for Systemic Sclerosis: A Retrospective Multicenter Observational Study - Kyung-Ann LEE; Bo Young KIM; Sung Jae CHOI; Seong-Kyu KIM; Sang-Hyon KIM; Hyun-Sook KIM (Archives of Rheumatology, 2020)
Objectives: This study aims to assess the efficacy and safety of mycophenolate mofetil (MMF) on lung function and skin thickness in Korean patients with systemic sclerosis-interstitial lung disease (SSc-ILD) in a real-world setting. Patients and methods: This retrospective, medical chart-based study was performed at four centers in South Korea and included 34 patients (2 males, 32 females; median age 50.5 years; range, 25 to 72 years) with SSc-ILD. We investigated changes in forced vital capacity (FVC), diffusion capacity of the lung for carbon monoxide (DLCO), and modified Rodnan skin score (mRSS) according to MMF treatment for 24 months. Results: The mean dose and treatment duration of MMF were 1,338.2±439.0 mg/day and 13.1±9.3 months, respectively. Although FVC decreased significantly at 15 months, FVC and DLCO did not change significantly during treatment with MMF. Median mRSS decreased significantly from 17.5 (2-40) to 10.5 (2-40) units (p<0.0001). Thirteen patients (38.24%) discontinued treatment with MMF [treatment duration 8.00 (3.0-24.0) months]; the predominant cause of discontinuation was of economic nature (46.15%). No serious adverse events were reported. Conclusion: This real-world based study supports the role of MMF in the stabilization of lung function and the improvement in skin thickness with an acceptable safety profile in patients with SSc. Economic burden is the main cause of discontinued treatment with MMF.